الستيروئيدات القشرية الانشاقية وخطر الداء السكري عند المسنين - حجازية, مالك; المرعي, منيف; الرستم, مازن (Latakia University Journal -Medical Sciences Series, 2019)
أجريت هذه الدراسة في قسم الأمراض الباطنة لمشفى الأسد الجامعي في اللاذقية خلال العام 2008-2009، وشملت 70 مريضاً مسناً يعانون من آفات قصبية انسدادية مزمنة، ويستخدمون الستيروئيدات القشرية الانشاقية ولا يشكون من داء سكري مثبت ومعالج عند دخولهم الدراسة, إذ تم تقسيم المرضى إلى مجموعتين: الأولى: مستخدمي الستيروئيد القشري الانشاقي لوحده.الثانية: مستخدمي الستيروئيد القشري الانشاقي مع التعرض للستيروئيد القشري الجهازي,كماتم التمييز بين مستخدمي الجرعات الدنيا والعليا من الستيروئيد القشري الانشاقي في كلا المجموعتين, عندئذٍ تمت مراقبة المرضى لتحري تطور داء سكري لديهم. إذ تبين تطور داء سكري مثبت ومعالج بنسبة قليلة جداًهي:مريض واحد(2,6%) لمرضى المجموعة الأولى ومريض واحد (4,5%) لمرضى المجموعة الثانية كذلك لاحظنا زيادة نسبة الإصابة بالداء السكري باستخدام الجرعات العالية من الستيروئيد القشري الإنشاقي. This study was carried out in the Department of Internal Medicine at Al-Assad University Hospital in Lattakia during the year 2008-2009, and included 70 patients with COPD (Chronic Obstructive Pulmonary Disease); they were using inhaled corticosteroids but had no diabetes. Then, we divided them into two groups: The first included the users of inhaled corticosteroids alone. The second included the users of inhaled corticosteroids who had been exposed to systemic corticosteroids; in such groups, we referred to the users of low and high doses of inhaled corticosteroids in both groups, We found diagnostic diabetes at a very low percentage: of patients of the first group, 1 patient (2.6%) and of patients of the second, 1 patient(4.5%). We noticed that diabetes increased by using high doses of inhaled corticosteroids.